PEMERIKSAAN KADAR HEMOGLOBIN SEBAGAI IDENTIFIKASI AWAL ANEMIA PADA KOMUNITAS VEGETARIAN DI WILAYAH JAKARTA BARAT - Chairlan Chairlan; Mardiana Mardiana; Husjain Djajaningrat (Poltekkes Kemenkes Jakarta III, 2017)
Vegetarian vegans are at risk of anemia, it maybe because the food intake lacks the nutritional components necessery for hemoglobin formation. The aims of this study is to determine of hemoglobin (Hb) concentration in vegetarian as an indication of suffering of anemia. The study was conducted on 57 vegetarian vegan people which was eligible by inclusioncriterion. The independent variables in this study were gender, age, and duration of being vegetarian, while the dependent variable was hemoglobin concentration. Hemoglobin concentrations of each subject was measured by Cyanmethehemoglobinmethod. Bivariate analyzed was done bychi square test and by descriptively bycomparing Hb concentration with reference value. There are four people (7.0%)out of the 57 subjects studied who had Hb concentrations below the reference value, consisting of one male and three female. The male and female subjects between the ages 12-25 years had the best mean Hb concentrations compared to others aged groups. T test showed no corralation between Hb concentrations with gender, age, and duration of being vegetarian (P ≥ 0.05).That may be due to the good-vegetarian nutritional intake.The result also show that long being vegetarian does not cause low Hb concentration, and refuse the hypothesis that it will cause low Hb concentration.